Numerical study on suppression of thermoacoustic oscillation in cryogenic helium pipeline system. (July 2021) - Hu, Lulu; Yang, Peng; Chen, Pengfan; Liu, Yingwen
Highlights: A solution to control thermoacoustic oscillations is proposed. Dual temperature gradient is developed by the introduction of the adjustment tube. The influence of parameters sensitive to the oscillation-free operation is revealed. The phase relationship between acoustic waves is identified. Abstract: Suppression of gas oscillation is essential to realize the stable operation of the cryogenic helium piping systems. In the current study, a structural solution, that is, a tube is connected to the main pipe as an adjustment accessory to control unfavourable gas oscillations. The model with dual temperature gradients is developed by introducing an adjustment tube. The effects of the parameter sensitive to the distribution of the dual temperature gradients on the thermoacoustic oscillation (TAO) characteristics are revealed. The results demonstrate that the asymmetry of the temperature distribution and a large frequency deviation makes it easier to achieve the oscillation-free operation of the system. At the initial start-up stage, the phase relationship between the acoustic waves is shown. As the cold length to warm length ratio decreases, the phase difference between sound waves increases, and the oscillation-free operation is accomplished when the cold length to warm length ratio is 0.11. Therefore, an approach of adjusting the length ratio in the adjustment tube can control thermoacoustic oscillations of cryogenic fluid.